Safety and Immunogenicity of a Heterologous Prime-Boost Ebola Virus Vaccine Regimen in Healthy Adults in the United Kingdom and Senegal. (8th November 2018) - Venkatraman, Navin; Ndiaye, Birahim Pierre; Bowyer, Georgina; Wade, Djibril; Sridhar, Saranya; Wright, Daniel; Powlson, Jonathan; Ndiaye, Ibrahima; Dièye, Siry; Thompson, Craig; Bakhoum, Momar; Morter, Richard; et al.
Abstract: Background: The 2014 West African outbreak of Ebola virus disease highlighted the urgent need to develop an effective Ebola vaccine. Methods: We undertook 2 phase 1 studies assessing safety and immunogenicity of the viral vector modified vaccinia Ankara virus vectored Ebola Zaire vaccine (MVA-EBO-Z), manufactured rapidly on a new duck cell line either alone or in a heterologous prime-boost regimen with recombinant chimpanzee adenovirus type 3 vectored Ebola Zaire vaccine (ChAd3-EBO-Z) followed by MVA-EBO-Z. Adult volunteers in the United Kingdom (n = 38) and Senegal (n = 40) were vaccinated and an accelerated 1-week prime-boost regimen was assessed in Senegal. Safety was assessed by active and passive collection of local and systemic adverse events. Results: The standard and accelerated heterologous prime-boost regimens were well-tolerated and elicited potent cellular and humoral immunogenicity in the United Kingdom and Senegal, but vaccine-induced antibody responses were significantly lower in Senegal. Cellular immune responses measured by flow cytometry were significantly greater in African vaccinees receiving ChAd3 and MVA vaccines in the same rather than the contralateral limb. Conclusions: MVA biomanufactured on an immortalized duck cell line shows potential for very large-scale manufacturing with lower cost of goods. This first trial of MVA-EBO-Z in humans encourages further testing in phase 2 studies, with the 1-week prime-boost interval regimen appearing to be particularly suitable for outbreak control. Clinical Trials Registration: NCT02451891; NCT02485912. Abstract : New vaccines are needed for outbreak pathogens and novel technologies to manufacture them. We describe 2 phase 1 clinical trials demonstrating safety and immunogenicity of a novel Ebola vaccine manufactured using an improved method to reduce costs and increase yield.